2021
DOI: 10.1108/md-03-2020-0349
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inter-organizational compatibility on knowledge transfer in cross-border M&As

Abstract: PurposeThe study adopts congruence theory to explore the structure of inter-organizational compatibility and its structural effects on knowledge transfer in cross-border merger and acquisitions (M&As).Design/methodology/approachThis paper built a moderated-mediation model that presented the relationship between inter-organizational compatibility and knowledge transfer. Regression analysis was conducted with 182 samples from China to examine the model and hypotheses.FindingsThe results indicate that inter-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Innovation is regarded to be an important source of competitive advantage. Previous research on innovation has found that, although enterprises must build strong in-house innovation capabilities, they also need to strengthen their relationships with suppliers and competitors to absorb critical knowledge and integrate existing knowledge with the creation of new knowledge (Arora et al, 2021;Qi et al, 2021). Alliances between actors in an ecosystem, therefore, can be a very useful activity, wherein Allies can increase the success rate of innovation and learn from their relationships (Ferreira et al, 2020).…”
Section: Ecosystem Alliances and Innovationmentioning
confidence: 99%
“…Innovation is regarded to be an important source of competitive advantage. Previous research on innovation has found that, although enterprises must build strong in-house innovation capabilities, they also need to strengthen their relationships with suppliers and competitors to absorb critical knowledge and integrate existing knowledge with the creation of new knowledge (Arora et al, 2021;Qi et al, 2021). Alliances between actors in an ecosystem, therefore, can be a very useful activity, wherein Allies can increase the success rate of innovation and learn from their relationships (Ferreira et al, 2020).…”
Section: Ecosystem Alliances and Innovationmentioning
confidence: 99%
“…Moreover, researchers have increasingly turned their attention to sociocultural variables that have an impact on the success or failure of M&As in general and the PMI process in particular (Buono et al, 1985;Cartwright and Schoenberg, 2006;Dackert et al, 2003;Halsall, 2008;Tetenbaum, 1999;Vaara, 2000;Stahl et al, 2011;Stahl and Voigt, 2008;Khan et al, 2020;van den Steen, 2010). Hence, cultural integration and compatibility, as well as the process of acculturation, have been identified as crucial factors for understanding the outcomes of M&A (Qi et al, 2021;Larsson and Lubatkin, 2001;van den Steen, 2010;Stahl and Voigt, 2008;Cartwright and Schoenberg, 2006;Weber, 1996). Existing research generally suggests that cultural differences between the acquirer and acquired tend to produce negative effects on the PMI process, and scholars have explored the nature and characteristics of these differences on multiple cultural levels (Graebner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several works on PMI have taken a look at the relevance of media discourse (e.g. Halsall, 2008;Hellgren et al, 2002;Kuronen et al, 2005;Vaara and Tienari, 2002), political ideologies and differing national cultures (see Avetisyan et al, 2020;Fehrenbacher et al, 2018;Meyer and Altenborg, 2007;Halsall, 2008;Morosini et al, 1998;Qi et al, 2021;Vaara et al, 2003), but, apart from these narrow or nationally-focused perspectives, we know surprisingly little about how macro-level societal factors and their interplay affect organizational cultures in the context of PMI. As such, despite the richness of research on PMI, there is a pressing need to employ alternative theoretical frameworks, conceptualizations and methods, and to avoid conducting research work in the field in silos of increasing specialization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations